2005
DOI: 10.1590/s1678-97412005000100016
|View full text |Cite
|
Sign up to set email alerts
|

<![CDATA[<B>Infective valve endocarditis treated by surgery</B>: <B>analysis of 64 cases</B>]]>

Abstract: Objective: To identify some aspects of infective valve endocarditis treated by heart surgery, as well as antibiotic therapy, in a public hospital in the city of Fortaleza, Ceará state, Brazil, from 1988 to 2003. Method: A retrospective and observational study was performed of 64 patients with infective valve endocarditis who required aortic and/or mitral valve replacement, tricuspid vegectomy and repair or pulmonary valve valvulectomy, as well as antibiotic therapy, during their in-hospital stay. They were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…Still, the hospital mortality in patients with valvular abscess due to complications of IE has been reported as 19.2% in Brazilian patients [23]. Similarly, the present study found a hospital mortality rate of 17% at 30 days for patients undergoing CVS due to IE and prolonged ICU length of stay, probably reflecting the severity of sepsis in these individuals [24][25][26]. However, the anatomical location of the valve infection was similar among the groups, confirming the absence of its association with clinical complications, including mortality, reflecting results previously presented by Rostagno et al [13].…”
Section: Discussionsupporting
confidence: 63%
“…Still, the hospital mortality in patients with valvular abscess due to complications of IE has been reported as 19.2% in Brazilian patients [23]. Similarly, the present study found a hospital mortality rate of 17% at 30 days for patients undergoing CVS due to IE and prolonged ICU length of stay, probably reflecting the severity of sepsis in these individuals [24][25][26]. However, the anatomical location of the valve infection was similar among the groups, confirming the absence of its association with clinical complications, including mortality, reflecting results previously presented by Rostagno et al [13].…”
Section: Discussionsupporting
confidence: 63%
“…This was concordant with previous studies that have mentioned that these valves are the ones predominantly affected by the infectious process. 13 , 17 Mechanical and biological valves were similarly involved, which is also consistent with previous findings. 18 …”
Section: Discussionsupporting
confidence: 90%
“… 19 Taking into account studies conducted in Brazil, the frequency of negative blood cultures ranges from 40% to 58%. 13 , 15 , 17 , 20 Among these studies, only Pomerantzeff et al 13 specifically evaluated prosthesis endocarditis, and they reported that 50% of the blood cultures were negative (with the limitation of not describing prosthetic valve cultures).…”
Section: Discussionmentioning
confidence: 99%
“…5 Two recent Brazilian series of IE with 62 and 64 cases, respectively, did not feature S. bovis as an etiologic agent. 6 , 7 The goal of the present study was to describe the features of a series of cases of IE in a Brazilian scenario, establishing a comparison to what is known from the literature.…”
mentioning
confidence: 99%
“…Antibiotic use would rapidly clear S. bovis from the bloodstream, as it is very sensitive to penicillin. 6 , 7 , 19 …”
mentioning
confidence: 99%